Navigating cross-scalar challenges in adapting to climate change: insights from water planning in the Phoenix Metropolitan Area - Paul Schulze; Sara Meerow (Mitigation and Adaptation Strategies for Global Change, 2025)
Urban regions globally face increasing challenges in maintaining robust, reliable, and sustainable water systems in light of growing climatic and institutional uncertainties. Drought-induced supply reductions are increasingly concerning, particularly in arid regions such as the southwestern United States. This study critically examines adaptive water planning in the Phoenix Metropolitan Area (PMA) municipalities, focusing on the susceptibility of Colorado River water supplies. Drawing on a literature review and in-depth interviews with water planners, we identify and analyze key adaptation strategies, focusing on their perceived relevance, implementation dynamics, and socio-political constraints. Demand reduction, water reuse and recycling, and the recovery of stored water credits emerge as central, albeit unevenly pursued, strategies, each playing out across different spatial and temporal scales. However, our findings highlight that local adaptation planning in the PMA is shaped and constrained by persisting growth paradigms, institutional fragmentation, and complex basin-wide hydroclimatic and political uncertainties surrounding climate change impacts, overuse, and the 2026 renegotiation of Colorado River operations. While PMA municipalities benefit from diversified water portfolios, we argue that more anticipatory and transformative planning approaches and adaptation strategies are necessary to navigate and adapt to increasingly compound and cross-scalar water risks.
Keywords: 330; Urban water planning; Climate change adaptation; Uncertainty; Adaptation strategies; Cross-scalar challenges